1999
DOI: 10.7326/0003-4819-131-3-199908030-00002
|View full text |Cite
|
Sign up to set email alerts
|

Social Disengagement and Incident Cognitive Decline in Community-Dwelling Elderly Persons

Abstract: Social disengagement is a risk factor for cognitive impairment among elderly persons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

34
623
5
15

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 838 publications
(677 citation statements)
references
References 35 publications
34
623
5
15
Order By: Relevance
“…Group participation was associated with better SAH in a subgroup of older adults in a small Canadian study (Veenstra 2000). Social disengagement was associated with increased cognitive decline in a longitudinal study of older adults (Bassuk et al 1999). …”
Section: Group Participationmentioning
confidence: 94%
See 1 more Smart Citation
“…Group participation was associated with better SAH in a subgroup of older adults in a small Canadian study (Veenstra 2000). Social disengagement was associated with increased cognitive decline in a longitudinal study of older adults (Bassuk et al 1999). …”
Section: Group Participationmentioning
confidence: 94%
“…Increased social ties, defined as a composite of marital status, contact with friends/ relatives, church and group attendance, were associated with reduced mortality in some cohorts of older adults (Seeman et al 1987(Seeman et al , 1993. Social support has also been associated with decreased 5-year mortality among community-dwelling older adults (Blazer 1982), and social disengagement has been linked to increased odds of incident cognitive decline (Bassuk et al 1999). However, most studies have been done in community settings, and thus residents of care homes have not been widely studied.…”
Section: Introductionmentioning
confidence: 99%
“…Like personality, social engagement is a broad construct, comprising diverse elements, such as interpersonal attention, communication, imagination, and general social skills and experience. In some studies, individuals with KS have been shown to exhibit significant deficits in each of these areas of social engagement (van Rijn et al., 2008; Skakkebaek et al., 2013), which are in turn associated with poorer performance on tasks involving working memory and executive function, both in young adults (Seeman et al., 2011) and among the elderly (Bassuk, Glass, & Berkman, 1999; Krueger et al., 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Evidence on this issue is scant, but it appears that such benefits decrease among those over 80 (Fabrigoule et al 1995;Bassuk et al 1999). In particular, Avlund and colleagues report that the associations between social networks and disability are no longer significant in either men or women over 80 (Avlund et al 2004b).…”
Section: Introductionmentioning
confidence: 99%